Understanding Kanji Memorization Strategies Among Native Japanese Speakers: A Psycholinguistic Phenomenological Perspective - Linna Meilia Rasiban; Mery Andriani; Nanami Takazawa; Neneng Sutjiati; Noviyanti Aneros (JOLLT Journal of Languages and Language Teaching, 2026)
Kanji is one of the most complex writing systems because it requires the integration of visual, phonological, semantic, and orthographic processing simultaneously. In the digital era, increasing reliance on smartphones and automatic typing systems has reduced handwriting practices among Japanese speakers, contributing to difficulties in recalling and reproducing kanji accurately. Therefore, this study aims to identify the kanji memorization strategies used by native Japanese speakers and examine the factors influencing those strategies. This study employed a qualitative approach with a descriptive phenomenological design within a psycholinguistic framework. Data were collected through semi-structured interviews and online questionnaires involving eight native Japanese speakers aged 17–62 who actively use kanji in daily life. The instruments consisted of an interview guide and a questionnaire developed from kanji learning strategy classifications. Data were analyzed using thematic analysis. The findings reveal that native Japanese speakers employ multiple strategies, particularly repetitive writing, radical analysis, visual recognition, meaning association, contextual learning, and technology-assisted practices. Strategy selection is influenced by educational experiences, literacy environment, kanji complexity, motivation, learning preferences, and technological adaptation. The findings also indicate generational differences in strategy use, especially regarding increasing dependence on digital technology and declining handwriting frequency. Furthermore, kanji memorization is interpreted not only as a cognitive activity but also as a sociocultural practice related to discipline, persistence, and literacy identity. These findings contribute to the development of more contextual and culturally grounded kanji learning models.